Harmless comprehensive utilization method of liquid aluminum-chromium slag
Through high-temperature reduction smelting and hydrogen-argon mixed gas bottom blowing reduction technology in an arc furnace, the problem of high CaO content and hexavalent chromium content in chromium corundum does not meet safety standards, and the production of high purity and high value-added chromium corundum and chromium carbide is achieved.
Patent Information
- Application Number
- CN202411933157.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-21
AI Technical Summary
In the prior art, when preparing chromium corundum, the CaO content is too high, resulting in a decrease in hardness, flexural strength and density index. At the same time, the hexavalent chromium content does not meet safety standards, and the smelting process is complex and the energy consumption is high.
High-temperature liquid aluminum chromium slag is used as raw material and coke as reducing agent to perform high-temperature reduction and smelting in an arc furnace. By controlling the temperature and coke addition amount, the formation of Al3C4 is avoided, and the reaction between Cr2O3 and C is achieved to generate chromium carbide, and trace amounts of hexavalent chromium are reduced by bottom blowing by hydrogen-argon mixture.
It significantly improves the hardness, flexural strength and density of chromium corundum, reduces the CaO content, ensures the safety standards of hexavalent chromium, simplifies the process flow, saves energy, and achieves high purity and high value-added product production.
Smart Images

Figure CN119662986A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal material smelting, and in particular to a method for harmless comprehensive utilization of liquid aluminum-chromium slag. Background Art
[0002] Alumina-chrome slag is a solid slag produced by the aluminothermic process to smelt metallic chromium. It is named because its main components are aluminum oxide and chromium oxide. The annual output of alumina-chrome slag is about 100,000 tons. It is a typical chromium-containing solid waste with the characteristics of large output, complex composition, poor degradability and great environmental harm. With the continuous development of industrial technology, aluminum-chromium slag has been gradually used in the field of refractory materials since the 1970s. However, the hexavalent chromium in aluminum-chromium slag will cause environmental pollution. The latest "National List of Hazardous Wastes (2025 Edition)" in the waste category HW21 clearly stipulates that the smelting slag produced by the aluminothermic smelting of metallic chromium in the production process of ferrochromium alloy is a hazardous waste (code 314-003-21). Therefore, the chrome corundum products produced in many patents are all new hazardous wastes (hereinafter referred to as aluminum-chromium slag). However, Article 31 of the "Hazardous Waste Exemption Management List" in the "National List of Hazardous Wastes (2025 Edition)" points out that under the premise that environmental risks are controllable, a hazardous waste generated by one unit can be used as a substitute raw material for environmental governance or industrial raw material production by another unit, and its utilization process is not managed as hazardous waste.
[0003] Chinese invention patent publication number CN 104788112A discloses an electric fused corundum material and a production method thereof. In this method, the CaO content of the chrome corundum prepared by the electric fused reduction method of solid chrome aluminum slag is relatively high, which is 0.4%-0.8% (see paragraph
[0023] of the specification), which will lead to a decrease in the hardness, high temperature flexural strength, bulk density and other indicators of the chrome corundum.
[0004] The Chinese invention patent publication number CN 105568004A discloses a method for smelting metal chromium from aluminum-chromium slag in an electric arc furnace. The method uses solid aluminum-chromium slag as raw material, uses petroleum coke as a reducing agent, and calcium fluoride as a slag-making agent to obtain qualified metal chromium products. In order to obtain qualified metal chromium products, the method adds an oxidation and carbon removal process after the high-temperature smelting process. This process not only requires additional transfer, heating, and oxygen supplementation, but also has a complex production process and high equipment cost. In addition, a large amount of calcium oxide and calcium fluoride are added during the oxidation process, and excessive Ca sources are actively introduced, resulting in the upper layer of corundum products containing a large amount of CaO and Cr2O3, which will significantly affect the hardness, high-temperature flexural strength, bulk density and other properties of the product, restricting the application scope of corundum and its added value. Based on the above situation, the chrome corundum products prepared by the existing technology all belong to the category of hazardous waste, and the existing technology uses solid aluminum-chromium slag as raw material for production. At this time, the high-temperature liquid aluminum-chromium slag produced by smelting needs to be cooled, crushed and heated again, which has the disadvantages of complex production process, large equipment investment and high energy consumption. Therefore, aluminum-chromium slag urgently needs new process technology for development and utilization, turning waste into treasure, reducing environmental pollution and improving economic benefits. Summary of the invention
[0005] The purpose of the present invention is to solve the problem that the CaO content of chrome corundum prepared by the prior art is too high, which leads to the decrease of the hardness, high temperature flexural strength, bulk density and other indicators of chrome corundum, and the Cr in chrome corundum 6+ The content is about 0.0005%, which does not meet the requirements of the "National List of Hazardous Wastes (2025 Edition)". A method for the harmless comprehensive utilization of liquid aluminum-chromium slag is provided. The present invention uses high-temperature liquid aluminum-chromium slag produced in the process of metal chromium production as raw material, coke as a reducing agent, and smelts through an electric arc furnace to obtain high-value-added high-purity fused corundum, chromium carbide and other products, and uses hydrogen-argon mixed gas to perform bottom blowing to reduce trace hexavalent chromium. The present invention greatly saves energy, shortens the process flow, improves production efficiency, and obtains chromium corundum products that meet the requirements of the "National List of Hazardous Wastes (2025 Edition)".
[0006] The invention uses high-temperature liquid aluminum-chromium slag as raw material and coke as reducing agent, and performs high-temperature reduction smelting in a 3500-6300KVA three-phase electric arc furnace. The generation of Al3C4 is avoided by controlling the temperature and the amount of coke added. At the same time, Cr2O3 reacts with C to generate chromium carbide. Since the theoretical density of chromium carbide is 6.68g / cm 3 Much larger than the theoretical density of Al2O3 3.90g / cm 3, gradually settle in the molten state, thus achieving separation. Na2O and K2O react with C at high temperature to generate metal K and Na vapor, which evaporate after stirring. In addition, after high-temperature smelting is completed, the electrode is taken out, the arc furnace is moved out with special equipment and fixed in a designated position, and then the furnace liquid in the furnace body is blown with hydrogen-argon (10%-90% v / v) mixed gas to remove the trace Cr in the furnace. 6+ It is reduced to elemental chromium to obtain two high value-added products: high-purity fused corundum and chromium carbide.
[0007] The liquid aluminum-chromium slag used in the present invention is the upper red liquid in the metal chromium production process. The content of each component by mass percentage (average content of 50 furnaces) is shown in Table 1 below. It can be seen from Table 1 that the chemical composition of the aluminum-chromium slag is mainly Al2O3 and Cr2O3, in addition to a small amount of CaO, MgO, Fe2O3, SiO2 and other components.
[0008] Table 1
[0009] Serial number Main Ingredients content(%) 1 <![CDATA[Cr2O3]]> 15.5 2 <![CDATA[Cr 6+ ]]> 0.04 3 <![CDATA[Al2O3]]> 80.64 4 <![CDATA[Fe2O3]]> 0.11 5 <![CDATA[Na2O]]> 0.89 6 <![CDATA[K2O]]> 0.88 7 CaO 0.96 8 MgO 0.14 9 <![CDATA[SiO2]]> 0.30
[0010] The present invention is achieved through the following technical solutions:
[0011] The present invention provides a method for harmless comprehensive utilization of liquid aluminum-chromium slag, comprising the following steps:
[0012] (1) taking high-temperature liquid aluminum-chromium slag and placing it in a ladle, and pouring it into an electric arc furnace for standby use; taking a certain amount of coke particles and pouring it into the electric arc furnace;
[0013] (2) Start an electric arc furnace, insert a graphite electrode into the above-mentioned mixture, use the high temperature generated by the graphite electrode arc to make the mixture react, and make the materials in the furnace tumble until the reaction is completed to obtain an upper layer of α-Al2O3 phase high-purity fused corundum and a lower layer of chromium carbide; wherein the chromium carbide contains Cr3C2 and Cr7C3, and the reaction equation occurring in the lower layer is as follows:
[0014] 7Cr2O3+27C=2Cr7C3+21CO
[0015] 3Cr7C3+5C=7Cr3C2
[0016] (3) After the high-temperature reduction smelting is completed, the electrodes are taken out, the arc furnace is moved out using special equipment and fixed in a designated position, and then the furnace liquid in the furnace body is blown with hydrogen-argon mixed gas to remove the trace amount of Cr 6+ After the bottom blowing of hydrogen-argon mixed gas is completed, the blowing system is turned off, the arc furnace is dumped, and the high-purity fused corundum and chromium carbide are separated by slag balls, and poured into different molds for cooling;
[0017] (4) The high-purity fused corundum is crushed, screened, and packaged to obtain a high-purity fused corundum particle product; the surface of the chromium carbide is sandblasted to remove impurities, crushed, screened, and packaged to obtain a chromium carbide product.
[0018] Preferably, in step (1), the mass ratio of coke particles to high-temperature liquid aluminum-chromium slag is (20-50):1000, the particle size of the coke particles is 0-5 mm, the fixed carbon is 83-84%, Si is less than 3%, and the moisture is less than 3%. If too little carbon source is added, the smelting products are chromium corundum, chromium carbide and metallic chromium. Too much carbon source will cause the upper layer of Al2O3 to form Al3C4, reducing the quality of corundum.
[0019] Preferably, the temperature of the high-temperature liquid aluminum-chromium slag is 2050-2300°C.
[0020] Preferably, the model of the electric arc furnace in step (2) is a 3500KVA-6300KVA three-phase electric arc furnace, the reaction temperature is 1900°C-2200°C, and the reaction time is 8-12h.
[0021] Preferably, in step (3), the volume ratio of hydrogen-argon mixed gas blown at the bottom of the electric arc furnace is 1:9-1:1, the flow rate is 2-30L / min, and the bottom blowing time is 5-30min. The present invention selects hydrogen-argon mixed gas bottom blowing because argon can stir the high-temperature solution in the furnace, so that the solution and coke particles are evenly distributed and react fully, and can also make impurities float and purify the product, while hydrogen is used to provide a reducing atmosphere to assist the coke particles in reducing hexavalent chromium.
[0022] Preferably, the density of the slag-blocking balls in step (3) is 4.2-6.2 g / cm 3 .
[0023] Preferably, the cooling time of the high-purity liquid corundum in step (4) is 24-72 hours.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. Directly using the liquid aluminum-chromium slag in the process of metal chromium smelting for carbonization reduction simplifies the cumbersome process of traditional solid slag, eliminates the steps of cooling, crushing, and reheating the liquid aluminum-chromium slag, significantly improves work efficiency, saves energy consumption, and thus reduces the overall processing cost.
[0026] 2. Use hydrogen-argon mixed gas to blow at the bottom. The hydrogen-argon mixed gas has a stirring effect. The hydrogen concentration is not high. Its main function is to deoxidize, provide a reducing atmosphere, and assist C in reducing Cr. 6+; Argon has the function of dehydrogenation and impurity removal. Through the insolubility and dilution effect of argon, it can take away the dissolved hydrogen in the molten steel, thereby reducing the hydrogen content and preventing hydrogen embrittlement. When hydrogen and argon work together, the dehydrogenation process can be further optimized through dynamic balance. Cr cannot be detected in corundum 6+ , in line with Cr 6+ The hazardous waste standard of no more than 5.0 mg / kg solves the problem that the "National Hazardous Waste List (2025 Edition)" stipulates that metal chromium smelting slag is a hazardous waste that cannot be discharged, and realizes zero discharge and harmless treatment of solid waste resources. At the same time, the chromium carbide prepared by this method has low impurities, high hardness and wear resistance, high temperature resistance and oxidation resistance, and stable chemical properties. It can be widely used in the metallurgical industry, electronics industry, high temperature resistant coatings, aerospace and other fields.
[0027] 3. High-purity fused corundum and chromium carbide are produced using liquid aluminum-aluminum-chromium slag as raw materials. The CaO content in the raw materials is extremely low, and no new calcium source is introduced during the smelting process. Compared with the corundum produced by the general patented method, the high-purity fused corundum prepared by this method has an Al2O3 content higher than 99%, and the content of impurities such as CaO is less than 0.15%. It has the advantages of high hardness, strong wear resistance, and high stability, and can be widely used in mechanical manufacturing, optoelectronics, chemical industry, environmental protection and other fields.
[0028] 4. The present invention can effectively remove the components (K and Na) in chromium corundum that are easily volatile during the high-temperature carbonization reduction process by regulating the electric melting conditions, purify the impurities in the electric arc furnace, and thus prepare electric melting corundum and chromium carbide with high added value and purity.
[0029] Instruction Manual
[0030] Figure 1 It is a schematic diagram of the overall process of the present invention, wherein: 1-smelting furnace, 2-ladle, 3-arc furnace, 4-coke particle batching tank, 5-negative pressure induced draft fan, 6-bottom blowing hole, 7-slag ball, 8-high purity fused corundum, 9-chromium carbide. DETAILED DESCRIPTION
[0031] In order to better explain the present invention and facilitate understanding of the technical solution of the present invention, it is now further described in conjunction with the drawings and embodiments. It should be understood that the specific embodiments of the present invention are only for illustrative purposes and are not intended to limit the present invention.
[0032] Example 1
[0033] A method for harmless comprehensive utilization of liquid aluminum-chromium slag in this embodiment is shown in the attached Figure 1 , including the following steps:
[0034] (1) Transfer and transportation of aluminum-chromium liquid slag: 5.0 tons of aluminum-chromium liquid slag with a temperature of 2090° C. after smelting in the metal chromium smelting furnace 1 is poured from the ladle 2 into the 3500KVA electric arc furnace 3 for insulation and standby use; the content of Cr2O3 in the aluminum-chromium liquid slag is 16.6%, and the content of Al2O3 is 79.8%;
[0035] (2) Adding coke particles: using a coke particle batching tank 4, 140 kg of coke particles crushed to a particle size of ≤5 mm are added to the above aluminum-chromium liquid slag, wherein the coke particles contain 83.4% fixed carbon, 2.6% Si, and 2.3% moisture;
[0036] (3) Carburization reduction reaction: start the electric arc furnace 3, insert the electrode into the mixture, use the high temperature generated by the graphite electrode arc to make the mixture react, control the reaction temperature to 1900°C-2200°C, and continue the reaction under this smelting condition for 9 hours. After the reaction is completed, the upper layer is a high-purity liquid fused corundum layer of α-Al2O3, and the chromium carbide settles to the bottom of the electric arc furnace due to its large specific gravity;
[0037] (4) Removal of Cr by bottom blowing with hydrogen-argon mixed gas 6+ After the high-temperature reduction smelting is completed, the electrodes are taken out, the arc furnace 3 is moved out by special equipment and fixed in a designated position, and the furnace liquid is bottom-blown from the bottom-blowing hole 6 with a hydrogen-argon (3:7, v / v) mixed gas while being blown by a negative pressure induced draft fan 5 to reduce trace Cr 6+ For single substance chromium, the gas flow rate is 10L / min, the bottom blowing time is 10min, and the blowing system is turned off after the bottom blowing of hydrogen-argon mixed gas is completed;
[0038] (5) Separation and crushing: After carbonization reduction and bottom gas blowing, the molten high-purity liquid corundum is poured into the fused corundum mold using the slag ball 7, and the chromium carbide at the bottom is placed in the chromium carbide mold; after cooling in the mold for 48 hours, sandblasting, impurity removal, crushing, screening, and packaging are performed to obtain high-purity fused-cast corundum bricks, high-purity fused corundum 8 particles and chromium carbide 9 products. The physical and chemical indicators of the high-purity fused corundum and chromium carbide obtained in this embodiment are shown in Table 2 and Table 3, respectively.
[0039] Example 2
[0040] A method for harmless comprehensive utilization of liquid aluminum-chromium slag in this embodiment is shown in the attached Figure 1 , including the following steps:
[0041] (1) Transfer and transportation of aluminum-chromium liquid slag: 5.0 tons of aluminum-chromium liquid slag with a temperature of 2101°C after smelting in the metal chromium smelting furnace 1 is poured from the ladle 2 into the 3500KVA electric arc furnace 3 for insulation and standby use; the content of Cr2O3 in the aluminum-chromium liquid slag is 16.5%, and the content of Al2O3 is 81.1%;
[0042] (2) Adding coke particles: using a coke particle batching tank 4, 100 kg of coke particles crushed to a particle size of ≤5 mm are added to the above aluminum-chromium liquid slag, wherein the coke particles contain 83.4% fixed carbon, 2.6% Si, and 2.3% moisture;
[0043] (3) Carburization reduction reaction: start the electric arc furnace 3, insert the electrode into the mixture, use the high temperature generated by the graphite electrode arc to make the mixture react, control the reaction temperature to 1900°C-2200°C, and continue the reaction under this smelting condition for 10 hours. After the reaction is completed, the upper layer is a high-purity liquid fused corundum layer of α-Al2O3, and the chromium carbide settles to the bottom of the electric arc furnace due to its large specific gravity;
[0044] (4) Removal of Cr by bottom blowing with hydrogen-argon mixed gas 6+ After the high-temperature reduction smelting is completed, the electrodes are taken out, the arc furnace 3 is moved out by special equipment and fixed in a designated position, and the furnace liquid in the furnace body is bottom-blown from the bottom-blowing hole 6 with a hydrogen-argon (3:7, v / v) mixed gas while being blown by a negative pressure induced draft fan 5 to reduce trace Cr 6+ For single element chromium, the gas flow rate is 15L / min, the bottom blowing time is 10min, and the blowing system is turned off after the bottom blowing of hydrogen-argon mixed gas is completed;
[0045] (5) Separation and crushing: After carbonization reduction and bottom gas blowing, the molten high-purity liquid corundum is poured into the fused corundum mold using the slag ball 7, and the chromium carbide at the bottom is placed in the chromium carbide mold; after cooling in the mold for 48 hours, sandblasting, impurity removal, crushing, screening, and packaging are performed to obtain high-purity fused-cast corundum bricks, high-purity fused corundum 8 particles and chromium carbide 9 products. The physical and chemical indicators of the high-purity fused corundum and chromium carbide obtained in this embodiment are shown in Table 2 and Table 3, respectively.
[0046] Example 3
[0047] A method for harmless comprehensive utilization of liquid aluminum-chromium slag in this embodiment is shown in the attached Figure 1 , including the following steps:
[0048] (1) Transfer and transportation of aluminum-chromium liquid slag: 5.0 tons of aluminum-chromium liquid slag with a temperature of 2160°C after smelting in the metal chromium smelting furnace 1 is poured from the ladle 2 into the 3500KVA electric arc furnace 3 for insulation and standby use; the content of Cr2O3 in the aluminum-chromium liquid slag is 16.2%, and the content of Al2O3 is 80.7%;
[0049] (2) Adding coke particles: using a coke particle batching tank 4, add 250 kg of coke particles crushed to a particle size of ≤5 mm into the above aluminum-chromium liquid slag, wherein the coke particles contain 83.84% fixed carbon, 2.2% Si, and 2.1% moisture;
[0050] (3) Carburization reduction reaction: start the electric arc furnace 3, insert the electrode into the mixture, use the high temperature generated by the graphite electrode arc to make the mixture react, control the reaction temperature to 1900°C-2200°C, and continue the reaction under this smelting condition for 10 hours. After the reaction is completed, the upper layer is a high-purity liquid fused corundum layer of α-Al2O3, and the chromium carbide settles to the bottom of the electric arc furnace due to its large specific gravity;
[0051] (4) Removal of Cr by bottom blowing with hydrogen-argon mixed gas 6+ After the high-temperature reduction smelting is completed, the electrodes are taken out, the arc furnace 3 is moved out by special equipment and fixed in a designated position, and the furnace liquid in the furnace body is bottom-blown from the bottom-blowing hole 6 with a hydrogen-argon (3:7, v / v) mixed gas while being blown by a negative pressure induced draft fan 5 to reduce trace Cr 6+ For single element chromium, the gas flow rate is 10L / min, the bottom blowing time is 5min, and the blowing system is turned off after the bottom blowing of hydrogen-argon mixed gas is completed;
[0052] (5) Separation and crushing: After carbonization reduction and bottom gas blowing, the molten high-purity liquid corundum is poured into the fused corundum mold using a slag ball, and the chromium carbide at the bottom is placed in the chromium carbide mold; after cooling in the mold for 48 hours, sandblasting, impurity removal, crushing, screening, and packaging are performed to obtain high-purity fused-cast corundum bricks, high-purity fused corundum particles 8 and chromium carbide 9 products. The physical and chemical indicators of the high-purity fused corundum and chromium carbide obtained in this example are shown in Table 2 and Table 3, respectively.
[0053] Since the amount of coke particles added, the time and temperature of the carburization reduction reaction have a crucial influence on the quality of the final fused corundum and chromium carbide products, the present invention also designs comparative examples 1-3 for the amount of coke particles added, and comparative examples 4-6 for the time and temperature of the carburization reduction reaction.
[0054] Comparative Example 1
[0055] The difference between this comparative example and Example 1 is that coke particles are not added during the carbonization reduction process of this comparative example, and the rest is the same as Example 1.
[0056] Comparative Example 2
[0057] The difference between this comparative example and Example 1 is that the amount of coke particles added during the carbonization reduction process in this comparative example is 40 kg, and the rest is the same as Example 1.
[0058] Comparative Example 3
[0059] The difference between this comparative example and Example 1 is that the amount of coke particles added in this comparative example is 275 kg, and the rest is the same as Example 1.
[0060] Comparative Example 4
[0061] The difference between this comparative example and Example 1 is that the smelting reaction time in step (2) provided in this comparative example is 6 hours, and the rest is the same as Example 1.
[0062] Comparative Example 5
[0063] The difference between this comparative example and Example 1 is that the smelting reaction time in step (2) provided in this comparative example is 16 hours, and the rest is the same as Example 1.
[0064] Comparative Example 6
[0065] The difference between this comparative example and Example 1 is that the carbonization reduction reaction temperature provided in this comparative example is 1600° C.-1800° C., and the rest is the same as Example 1.
[0066] The high-purity fused corundum and chromium carbide obtained in Examples 1-3 of the present invention and Comparative Examples 1-6 were tested for physical and chemical properties, respectively. The experimental results are shown in Tables 2 and 3.
[0067] Table 2 Physical and chemical indicators of high purity fused corundum
[0068]
[0069] Table 3 Physical and chemical indicators of chromium carbide
[0070]
[0071]
[0072] From Table 2 above, Cr in Examples 1-3 of the present invention and Comparative Examples 1-6 6+ The contents of Cr 6+ The hazardous waste standard of no more than 5.0 mg / kg solves the problem of metallic chromium smelting slag being designated as hazardous waste that cannot be discharged in the "National List of Hazardous Wastes (2025 Edition)", and achieves zero emission and harmless treatment of solid waste resources.
[0073] The quality of high-purity corundum is mainly reflected by the content of Al2O3 and Cr2O3. The higher the content of Al2O3, the better the quality of the corundum, and the lower the content of Cr2O3, the better the quality of the corundum. The quality of chromium carbide is mainly reflected by the sum of the contents of chromium and carbon. If it is greater than 99%, it means that the quality of chromium carbide is good. It can be seen from the physical and chemical indicators of high-purity fused corundum in Table 2 that the content of Al2O3 in Examples 1-3 of the present invention and Comparative Example 5 is greater than 99%, and the quality of corundum is good. The content of Cr2O3 in Comparative Example 1, Comparative Example 2, Comparative Example 4 and Comparative Example 6 is relatively high, so the quality of the corundum is not good. This is because in Comparative Example 1, coke particles are not added during the carbonization reduction process, so chromium corundum containing hexavalent chromium (Cr2O3) and metallic chromium are obtained, with only a small amount of chromium carbide (11.38%); in Comparative Example 2, a small amount of coke is added, and the purity of the obtained corundum is not high (87.65%), and the content of Cr2O3 is 9.12%; in Comparative Example 3, too much coke particles (275 kg) are added, and aluminum oxide Al2O3 will be converted into aluminum carbide Al3C4 during the corundum production process under this addition amount, affecting the quality of the corundum; in Comparative Examples 4 and 5, the reaction time is controlled. If the time is too short, high-purity corundum cannot be obtained, and if it is too long, it will have little effect but waste energy; in Comparative Example 6, the reaction temperature is controlled. The carbonization reduction reaction temperature is too low, so the product obtained is not high-purity fused corundum, and the content of Cr2O3 is 13.85%. It can be seen from Table 3 that except for Comparative Example 1 in which the sum of the chromium and carbon contents is low due to the absence of added coke particles, the sum of the masses of chromium carbides in other comparative examples is greater than 99%, indicating that controlling the time and temperature of the carburization reduction reaction has little effect on the chromium carbide.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for harmless comprehensive utilization of liquid aluminum-chromium slag, characterized in that: The steps include: (1) Take high-temperature liquid aluminum-chromium slag and place it in a ladle, then pour it into an electric arc furnace for standby use; take a certain amount of coke particles and pour them into the electric arc furnace; (2) starting an electric arc furnace, inserting a graphite electrode into the above-mentioned mixture, using the high temperature generated by the electric arc of the graphite electrode to react the mixture, and causing the materials in the furnace to tumble until the reaction is completed to obtain an upper layer of α-Al2O3 phase high-purity fused corundum and a lower layer of chromium carbide; (3) After high-temperature reduction smelting is completed, the electrodes are taken out, the arc furnace is moved out using special equipment and fixed in a designated position, and then hydrogen-argon mixed gas is blown from the bottom of the furnace body to remove trace amounts of Cr 6+ After the bottom blowing of hydrogen-argon mixed gas is completed, the blowing system is turned off, the arc furnace is dumped, and the high-purity fused corundum and chromium carbide are separated by slag balls, and poured into different molds for cooling; (4) The high-purity fused corundum is crushed, screened, and packaged to obtain high-purity fused corundum particle products; the surface of chromium carbide is sandblasted to remove impurities, crushed, screened, and packaged to obtain chromium carbide products.
2. The method for harmless comprehensive utilization of liquid aluminum-chromium slag according to claim 1, characterized in that: In the step (1), the mass ratio of coke particles to high-temperature liquid aluminum-chromium slag is (20-50):1000, the particle size of the coke particles is 0-5 mm, the fixed carbon content is 83-84%, Si is less than 3%, and the moisture content is less than 3%.
3. The method for harmless comprehensive utilization of liquid aluminum-chromium slag according to claim 1, characterized in that: The temperature of the high-temperature liquid aluminum-chromium slag is 2050-2300°C.
4. The method for harmless comprehensive utilization of liquid aluminum-chromium slag according to claim 1, characterized in that: The model of the electric arc furnace in step (2) is a 3500 KVA-6300 KVA three-phase electric arc furnace, the reaction temperature is 1900°C-2200°C, and the reaction time is 8-12 h.
5. The method for harmless comprehensive utilization of liquid aluminum-chromium slag according to claim 1, characterized in that: The steps (3) The volume ratio of hydrogen-argon mixed gas for bottom blowing in the electric arc furnace is 1:9-1:1, the flow rate is 2-30 L / min, and the bottom blowing time is 5-30 min.
6. The method for harmless comprehensive utilization of liquid aluminum-chromium slag according to claim 1, characterized in that: The steps (3) The density of the middle slag ball is 4.2-6.2 g / cm 3 .
7. The method for harmless comprehensive utilization of liquid aluminum-chromium slag according to claim 1, characterized in that: The cooling time of the high-purity liquid corundum in step (4) is 24-72 h.
Citation Information
Patent Citations
Fused alumina material and production method thereof
CN104788112A
Method for smelting chromium metal from aluminum-chromium slag in electric arc furnace
CN105568004A